An integrative approach underscores the taxonomic status of Lamellidens exolescens, a freshwater mussel from the Oriental tropics (Bivalvia: Unionidae). Issue 3 (4th May 2017) - Konopleva, Ekaterina S.; Bolotov, Ivan N.; Vikhrev, Ilya V.; Gofarov, Mikhail Y.; Kondakov, Alexander V.
Abstract : The Oriental Region harbours the second richest fauna of freshwater bivalves in the world, including many endangered endemic taxa. However, the Oriental fauna of the Unionidae have been very poorly studied using an integrative taxonomic approach, which may provide reasonable revisions of complicated (cryptic) taxa based on morphological, molecular, biogeographic and ecological evidence. Here, we present the first example of an integrative taxonomic revision concerning the status of Unio exolescens Gould (1843 ), a nominal mussel taxon that was accepted as a valid species within the genus Trapezoideus Simpson (1900). Currently, Trapezoideus exolescens is considered the type of the genus as far as the originally designated type species, U. foliaceus Gould (1843 ), was considered to be a synonym of T. exolescens . Using nucleotide sequences obtained from mitochondrial (COI and 16S rRNA) and nuclear (28S rDNA) genes, we found that the topotypes of Unio exolescens Gould (1843 ) cluster together with representatives of another mussel genus, Lamellidens Simpson (1900). Based on these results and on morphological data, we transfer Unio exolescens Gould (1843 ) from Trapezoideus to Lamellidens and propose Lamellidens exolescens (Gould, 1843 ) comb. nov. In addition, we revisited the status of Unio foliaceus Gould (1843 ) as a valid species and the type of the genus Trapezoideus based on the morphological study of the type specimen, although a question concerning the true position of this taxon is still open because its molecular sequences are not available. Our findings highlight that an integrative taxonomic approach is an important tool, particularly when dealing with such species-rich Unionidae fauna as those of the Oriental Realm.